Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Tevtia, Amit K.; Singh, R. P. (Polymer Degradation and Stability, 2006)
The stabilization of polyolefins against gamma-sterilization has been studied with single or binary additive system. The present attempt is to utilize synergistic mixtures of stabilizers which are approved for food contact applications. Ethylene-propylene (EP) copolymer has been melt-mixed with hindered amine stabilizers (HAS), phenolic antioxidants and organo-phosphites (hydroperoxide decomposer). Samples were sterilized with different doses of gamma-radiation. Stabilization was characterized in terms of changes in the functional groups (oxidation products), tensile properties, yellowing and surface morphology by FTIR spectroscopy, Instron, colorimetry (reflectance) and scanning electron microscopy (SEM), respectively. Results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol system. Among phenol containing systems, where we mostly observe discoloration due to the oxidation of hindered phenol and the combination of secondary HAS, tertiary HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The mixture of secondary HAS and tertiary HAS, has shown antagonistic effect of stabilization whereas their combination with organo-phosphite has exhibited synergistic effect of stabilization even at higher doses of gamma-sterilization. The effects have been explained through the interaction between the stabilizers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Antioxidants; discoloration; ethylene-propylene copolymer; gamma-sterilization; stabilization; tensile properties

In vitro regeneration of semecarpus anacardium L. from axenic seedling-derived nodal explants - Panda, Bhuban Mohan; Hazra, Sulekha (Trees-Structure and Function, 2010)
Semecarpus anacardium (Anacardiaceae), a deciduous forest tree, is a potent source of medicinal compounds. Poor seed viability of this species limits the conventional propagation practice. Proliferation of shoots from axillary meristem was achieved in semisolid WPM medium supplemented with BAP 4.44 mu M and KN 4.64 mu M. Factors including culture vessels, gelling agents and antioxidants were identified and optimized for proliferation and growth of shoots in vitro. Cotton-plugged culture vessels were more favorable. Phytagel 0.2% as gelling agent and activated charcoal 0.2% as antioxidant were superior to other agents and antioxidants tested. All the shoots rooted in half-strength WPM liquid medium with IBA 2.46 mu M. Rooted shoots survived (91%) in the soil-sand 1:1 mixture. Ex vitro rooting of shoots and hardening of plants were achieved in 80% of the explants in the soil-sand mixture. Hardened plants were maintained in a greenhouse. This is the first report on in vitro regeneration of Semecarpus anacardium.
Keywords: Antioxidants; Culture vessels; Ex vitro rooting; Gelling agents; Medicinal tree; micropropagation

Antioxidative metabolites synthesized by marine pigmented vibrio sp and its protection on oxidative deterioration of membrane lipids - Pawar, Ravindra; Mohandass, Chellandi; Dastager, Syed Gulam; Kolekar, Yogesh M.; Malwankar, Rahul (Applied Biochemistry and Biotechnology, 2016)
Bacterial strain Vibrio sp. (PIGB 184) isolated from water samples of the Arabian Sea and identified through 16S rRNA demonstrated the production of pigmentary antioxidants with higher ABTS activities 90.9 +/- 0.42 % in comparison with the standard commercial pigmented antioxidant, quercetin 88.8 +/- 1.4 %. Antioxidative metabolites of this strain substantially inhibit the lipid peroxidation (LPO) reactions tested in sheep liver and brain. The antioxidant compounds produced by the Vibrio sp. (PIGB 184), analysed by GC-MS, reveals that it is composed mostly of phenol, 2,4-bis(1,1-dimethylethyl) and pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro-3-(2-methylpropyl). The interrelationship assessed between LPO and the phenolic compounds showed significant correlation with anti-LPO properties (R (2) = 0.9698 to 0.9861). These compounds are responsible for obstruction of harmful radical associated biochemical reactions in biological systems. Pigmented metabolites also tested for attributive biological properties against pathogenic bacteria showed prominent inhibition towards Gram-positive organisms (31.25 to 62.5 mu g ml(-1)). From this study, it may be suggested that the marine bacterium PIGB 184 could be used as a potential bio-resource for antioxidants and needs to be worked out for mass production.
Keywords: Antioxidants; Lipid peroxidation; Marine pigmented bacteria; Pathogen inhibition; Phenolics

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin

Phytochemical profile, anti-oxidant, anti-inflammatory, and anti-proliferative activities of Pogostemon deccanensis essential oils - Kumar, Vinay; Shriram, Varsha; Bhagat, Rani; Khare, Tushar; Kapse, Shivanjali; Kadoo, Narendra (3 Biotech, 2019)
Essential oils (EOs) obtained from aerial parts of Pogostemon deccanensis were analyzed for GC-MS profiling, and evaluated for antioxidant, anti-inflammatory, and anti-proliferative activities. GC-MS analysis revealed a total of 47 constituents, establishing the EOs rich in sesquiterpene with >20 sesquiterpenes constituting around 77% of the total EO yield. Major constituents included Curzerene (Benzofuran, 6-ethenyl-4,5,6,7-tetrahydro-3,6-dimethyl-5-isopropenyl-, trans-) (26.39%) and epi-Cadinol (22.68%), Ethanone, 1-(2,4,6-trihydroxyphenyl) (6.83%, Acetophenones), and Boldenone (3.47%, anabolic steroid). EOs found to be rich in phytochemicals attributed for antioxidant potentials of aromatic/medicinal plants, viz., flavonoids (2.71 mu g quercetin equivalents g(-1) EO), total phenols (3.94 mu g gallic acid equivalents (GAE) g(-1) EO), carotenoids (14.3 mu g -carotene equivalents g(-1) EO), and ascorbic acid (2.21 mu g ascorbic acid equivalents g(-1) EO). P. deccanensis EOs exhibited striking antioxidant activities assessed by wide range of assays including ferric reducing antioxidant potential (FRAP, 255.3 GAE at 2 mu g mL(-1) EO), total antioxidant activity (TAA, 264.3 GAE at 2 mu g ml(-1)) of EO, DPPH (65% inhibition at 2 mu g mL(-1)), and OH (58% inhibition at 2 mu g mL(-1)) scavenging. Interestingly, EOs showed considerably higher anti-lipid peroxidation activity than the standard antioxidant molecule ascorbic acid, with 50% protection by 1.29 mu g mL(-1) EO against 20.0 mu g mL(-1) standard. EOs showed strong anti-inflammatory activity with 50% inhibition at 1.95 mu g mL(-1) EO. The anti-proliferative activity of EOs was tested against mouse cancer cell line and the EOs proved a potent anti-proliferative agent with only 2.1% cell survival at 2 mu g mL(-1) EO, whereas the EOs were largely non-toxic-to-normal (non-cancerous) cells with approximately 80% cell survival at the 2 mu g mL(-1) EOs. This being the first attempt of phytochemical profiling and wide array of biological activities of P. deccanensis EOs holds significance as the striking activities were observed at very low concentrations, in some cases at lower than the commercial standards, and has, therefore, great potential for pharmaceutical or commercial exploration.
Keywords: Anti-inflammatory activity; Anti-proliferative activity; Antioxidants; Cytotoxicity; Essential oils